Stem Cells, Hematopoiesis and Lineage Tracing: Transplantation-Centric Views and Beyond - Konturek-Ciesla, Anna; Bryder, David (Frontiers in Cell and Developmental Biology, 2022)
The production of mature blood cells, or hematopoiesis, is essential for organismal health and homeostasis. In this developmental cascade, hematopoietic stem cells (HSCs) differentiate into intermediate progenitor types, that subsequently give rise to the many distinct blood cell lineages. In this review, we describe tools and methods that permit for temporal and native clonal-level HSC lineage tracing in the mouse, and that can now be combined with emerging single-cell molecular analyses. We integrate new insights derived from such experimental paradigms to past knowledge, which has predominantly been derived from transplantation-based approaches. Finally, we outline novel strategies and current knowledge derived from studies aimed to trace human HSC-derived hematopoiesis.